Nursing training center in teaching the values of life care and health - M Sánchez; F. Herrera; M Socarras (Universidad del Magdalena, 2013)
Reflection paper on research, assuming the documentary research and hermeneutics for its comprehensibility in "the process of training nurses to enhance the mission of being a caregiver for life and health of himself and others", his thesis "The health care training and this relationship should be derived through the empowerment of knowledge promoted and gestated from pedagogical ethics "focused education emphasizing human condition and its effects on quality of life.